2004
DOI: 10.1097/00008506-200401000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Propofol and Clonidine on Cerebral Blood Flow Velocity and Carbon Dioxide Reactivity in the Middle Cerebral Artery

Abstract: This study was designed to evaluate the effects of propofol alone and propofol-clonidine combination on human middle cerebral artery blood flow velocity (Vmca) and cerebrovascular carbon dioxide (CO2) response by using transcranial Doppler ultrasonography. Mean Vmca in response to changes in arterial partial pressure of CO2 (Paco2) was determined under the following conditions: awake (group 1), propofol anesthesia (group 2), and combined propofol-clonidine anesthesia (group 3). Normocapnic, hypercapnic, and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…Our study findings demonstrated that propofol reduced V MCA . Similar results have been reported by many authors analysing V MCA during the use of anaesthetics [53,54]. A reduction in V MCA results from propofol-induced CBF depression [54].…”
Section: Discussionsupporting
confidence: 87%
“…Our study findings demonstrated that propofol reduced V MCA . Similar results have been reported by many authors analysing V MCA during the use of anaesthetics [53,54]. A reduction in V MCA results from propofol-induced CBF depression [54].…”
Section: Discussionsupporting
confidence: 87%
“…[17][18][19]22 With higher doses of propofol (>150 mg/kg/ min or TCI concentration 6 mg/mL), absolute reactivity is reduced but the relative reactivity remained intact. 20,21,23,24 At doses leading to a broadly equivalent depth of anesthesia, the CVR-CO 2 values are the highest with isoflurane and the lowest with propofol (Fig. 2).…”
Section: Hypercapnic Hypocapnicmentioning
confidence: 97%
“…There were no similar studies under propofol anesthesia (Table 6). 19 Endoh et al, 22 Sakai et al, 23 Mirzai et al 24 ) were used (desflurane data were not included in this figure, as there were no studies where CBF was evaluated using TCD under desflurane anesthesia). CBFV indicates cerebral blood flow velocity; CVR, cerebrovascular reactivity; MAC, minimum alveolar concentration; TCD, transcranial Doppler.…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 However, the relationship between these variables might be affected by differential effects of general anaesthesia and other changes during the peri-operative period. 11 A number of investigators have described a poor relationship between ScvO 2 and S O 2 , both in septic and surgical patients. [12][13][14][15] The aim of this study was to assess whether the continuous measurement of S O 2 and ScvO 2 using continuous fibreoptic technology would confirm the poor relationship between the variables in patients during and after cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%